The softening of human bladder cancer cells happens at an early stage of the malignancy process - Ramos, Jorge R.; Pabijan, Joanna; Garcia, Ricardo; Lekka, Malgorzata (Beilstein Journal of Nanotechnology, 2014)
Various studies have demonstrated that alterations in the deformability of cancerous cells are strongly linked to the actin cytoskeleton. By using atomic force microscopy (AFM), it is possible to determine such changes in a quantitative way in order to distinguish cancerous from non-malignant cells. In the work presented here, the elastic properties of human bladder cells were determined by means of AFM. The measurements show that non-malignant bladder HCV29 cells are stiffer (higher Young’s modulus) than cancerous cells (HTB-9, HT1376, and T24 cell lines). However, independently of the histological grade of the studied bladder cancer cells, all cancerous cells possess a similar level of the deformability of about a few kilopascals, significantly lower than non-malignant cells. This underlines the diagnostic character of stiffness that can be used as a biomarker of bladder cancer. Similar stiffness levels, observed for cancerous cells, cannot be fully explained by the organization of the actin cytoskeleton since it is different in all malignant cells. Our results underline that it is neither the spatial organization of the actin filaments nor the presence of stress fibers, but the overall density and their 3D-organization in a probing volume play the dominant role in controlling the elastic response of the cancerous cell to an external force.
Keywords: actin filaments; atomic force microscopy (AFM); bladder cells; cytoskeleton; elastic properties of cells; malignancy degree of cancer cells

(untitled) - Lu, P.; Weaver, V. M.; Werb, Z. (J. Cell Biol., 2012)

(untitled) - Goetz, J. G.; Minguet, S.; Navarro-Lérida, I.; Lazcano, J. J.; Samaniego, R.; Calvo, E.; Tello, M.; Osteso-Ibáñez, T.; Pellinen, T.; Echarri, A.; Cerezo, A.; Klein-Szanto, A. J. P.; et al. (Cell, 2011)

(untitled) - Li, Q. S.; Lee, G. Y. H.; Ong, C. N.; Lim, C. T. (Biochem. Biophys. Res. Commun., 2008)

(untitled) - Ludwig, T.; Kirmse, R.; Poole, K.; Schwarz, U. S. (Pfluegers Arch., 2008)

(untitled) - Lekka, M.; Laidler, P.; Gil, D.; Lekki, J.; Stachura, Z.; Hrynkiewicz, A. Z. (Eur. Biophys. J., 1999)

(untitled) - Lekka, M.; Gil, D.; Pogoda, K.; Dulińska-Litewka, J.; Jach, R.; Gostek, J.; Klymenko, O.; Prauzner-Bechcicki, S.; Stachura, Z.; Wiltowska-Zuber, J.; Okoń, K.; Laidler, P. (Arch. Biochem. Biophys., 2012)

(untitled) - Cross, S. E.; Jin, Y.-S.; Rao, J.; Gimzewski, J. K. (Nat. Nanotechnol., 2007)

(untitled) - Cross, S. E.; Jin, Y.-S.; Tondre, J.; Wong, R.; Rao, J.; Gimzewski, J. K. (Nanotechnology, 2008)

(untitled) - Reich, A.; Meurer, M.; Eckes, B.; Friedrichs, J.; Muller, D. J. (J. Cell. Mol. Med., 2009)

(untitled) - Faria, E. C.; Ma, N.; Gazi, E.; Gardner, P.; Brown, M.; Clarke, N. W.; Snook, R. D. (Analyst, 2008)

(untitled) - Prabhune, M.; Belge, G.; Dotzauer, A.; Bullerdiek, J.; Radmacher, M. (Micron, 2012)

(untitled) - Plodinec, M.; Loparic, M.; Monnier, C. A.; Obermann, E. C.; Zanetti-Dallenbach, R.; Oertle, P.; Hyotyla, J. T.; Aebi, U.; Bentires-Alj, M.; Lim, R. Y. H.; Schoenenberger, C.-A. (Nat. Nanotechnol., 2012)

(untitled) - Remmerbach, T. W.; Wottawah, F.; Dietrich, J.; Lincoln, B.; Wittekind, C.; Guck, J. (Cancer Res., 2009)

(untitled) - Lekka, M.; Laidler, P.; Ignacak, J.; Łabędź, M.; Lekki, J.; Struszczyk, H.; Stachura, Z.; Hrynkiewicz, A. Z. (Biochim. Biophys. Acta, Mol. Cell Res., 2001)

(untitled) - Wakatsuki, T.; Schwab, B.; Thompson, N. C.; Elson, E. L. (J. Cell Sci., 2001)

(untitled) - Rotsch, C.; Radmacher, M. (Biophys. J., 2000)

(untitled) - Pelling, A. E.; Dawson, D. W.; Carreon, D. M.; Christiansen, J. J.; Shen, R. R.; Teitell, M. A.; Gimzewski, J. K. (Nanomedicine, 2007)

(untitled) - Pogoda, K.; Jaczewska, J.; Wiltowska-Zuber, J.; Klymenko, O.; Zuber, K.; Fornal, M.; Lekka, M. (Eur. Biophys. J., 2012)

(untitled) - Cai, X.; Xing, X.; Cai, J.; Chen, Q.; Wu, S.; Huang, F. (Micron, 2010)

(untitled) - Sharma, S.; Santiskulvong, C.; Bentolila, L. A.; Rao, J.; Dorigo, O.; Gimzewski, J. K. (Nanomedicine, 2012)

(untitled) - Xu, W.; Mezencev, R.; Kim, B.; Wang, L.; McDonald, J.; Sulchek, T. (PLoS One, 2012)

(untitled) - Dos Remedios, C. G.; Chhabra, D.; Kekic, M.; Dedova, I. V.; Tsubakihara, M.; Berry, D. A.; Nosworthy, N. J. (Physiol. Rev., 2003)

(untitled) - Ketene, A. N.; Schmetz, E. M.; Roberts, P. C.; Agah, M. (Nanomedicine, 2012)

(untitled) - Huber, M. A.; Kraut, N.; Beug, H. (Curr. Opin. Cell Biol., 2005)

(untitled) - Yilmaz, M.; Christofori, G. (Cancer Metastasis Rev., 2009)

(untitled) - Hanahan, D.; Weinberg, R. A. (Cell, 2011)

(untitled) - Sneddon, I. N. (Int. J. Eng. Sci., 1965)

Design and Analysis of Experiments - Montgomery, C. D. (John Wiley & Sons, 1991)

(untitled) - Roduit, C.; Sekatski, S.; Dietler, G.; Catsicas, S.; Lafont, F.; Kasas, S. (Biophys. J., 2009)

(untitled) - Roduit, C.; Saha, B.; Alonso-Sarduy, L.; Volterra, A.; Dietler, G.; Kasas, S. (Nat. Methods, 2012)

(untitled) - O'Callaghan, R.; Job, K. M.; Dull, R. O.; Hlady, V. (Am. J. Physiol.: Lung Cell. Mol. Physiol., 2011)

(untitled) - Lekka, M.; Pogoda, K.; Gostek, J.; Klymenko, O.; Prauzner-Bechcicki, S.; Wiltowska-Zuber, J.; Jaczewska, J.; Lekki, J.; Stachura, Z. (Micron, 2012)

(untitled) - Dokukin, M. E.; Guz, N. V.; Gaikwad, R. M.; Woodworth, C. D.; Sokolov, I. (Phys. Rev. Lett., 2011)

(untitled) - Gavara, N.; Chadwick, R. S. (Nat. Nanotechnol., 2012)

(untitled) - Lekka, M.; Gil, D.; Dąbroś, W.; Jaczewska, J.; Kulik, A. J.; Lekki, J.; Stachura, Z.; Stachura, J.; Laidler, P. (J. Mol. Recognit., 2011)

(untitled) - Pharr, G. M.; Oliver, W. C.; Brotzen, F. R. (J. Mater. Res., 1992)